(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Sun orientation plays a significant role in architectural design. Concerning this, the sun-path diagram is a tool for developing more knowledge to improve the quality of building design. For achieving good and thermally comfortable building design, the sun shading device is essential to work. Therefore, this study performs an evaluation of the shading device in tropics utilising the sun-path diagram. This study evaluates the horizontal, vertical and louvre shadings on eight wind directions in Banda Aceh as a case study in tropics by adopting shadow angle protractor for superimposing the vertical (VSA) and horizontal shading angle (HSA) on the stereographic sun-path diagram to indicate the shadow and daylighting time. The result of this study proposes the suitable type of shading and the acceptable depth of horizontal shading dimensions for all of the orientations of the wind directions.